(3ZjK GdCOH GdPj CfSLe aj TQM dGejI GdYLes - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s; (3GdWZQGFj , GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO GdCUHgGfj GdWZQGfj, eDjO GdOjf CHh ESeGYjd,J (B513 (3g` s
(3ChdgG (B:s
(3hHYO, aEf GdbUjOI GdehSheI HdGejI GdYLe, QMe Gddg fGXe pYbOgG s
(3BNQgG (B:s
(3ce SbGfj ef KZQg cCS NeQ aQTaJ GdoSdGa ef CbMhGf gfG Je GdLRA GdChd ef ZjK GdCOH s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3JJab aj ChdgG eY GdfSNI GdChdis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs